PENGARUH TAX AVOIDANCE DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN SUBSEKTOR KOSMETIK DAN BARANG KEPERLUAN RUMAH TANGGA - Yasmin Ester; Francis Hutabarat (Jurnal Ilmiah Akuntansi Indonesia, 2020)
This study aims to see the effect of tax avoidance and profitability on firm value in cosmetic and houshold subsector companies listed on the Indonesia Stock Exchange. The sample in this study were 6 cosmetic and household subsector companies in 2015-2019. The variables in this study were 2 (two) independent variables and 1 (one) dependent variable, namely, tax avoidance as X1, profitability as X2 and firm value as Y. In the research analysis, researchers used the classical assumption test, descriptive statistics, coefficient of correlation, significance test and regression analysis. The results of this study are: 1) tax avoidance has no significant effect on firm value with a significant value of sig. 0.05 and t = -1.278, 2) profitability has a significant effect on firm value with a value of sig. 5% and t = -2.219.